Novel miRNA-SSRs for Improving Seed Hardness Trait of Pomegranate (Punica granatum L.) - Patil, Prakash Goudappa; Singh, Nripendra Vikram; Bohra, Abhishek; Jamma, Shivani; N, Manjunatha; C, Venkatesh S.; Karuppannan, Dhinesh Babu; Sharma, Jyotsana; Marathe, Rajiv A. (Frontiers in Genetics, 2022)
Present research discovered novel miRNA-SSRs for seed harness trait from 761 potential precursor miRNA sequences of pomegranate. SSR mining and BLASTx of the unique sequences identified 69 non-coding pre-miRNA sequences, which were then selected as query sequences for BLASTn homology search against pomegranate genome cv. Dabenzi. Sixty three true pri-miRNA contigs encoding 213 pre-miRNAs were predicted. Analysis of the resulting sequences enabled discovery of SSRs within pri-miRNA (227) and pre-miRNA sequences (79). A total of 132 miRNA-SSR were developed for seed hardness traits using 63 true pri-miRNAs, of which 46 were specific to pre-miRNAs. Through ePCR, 123 primers were validated and mapped on 8 Tunisia chromosomes. Further, 80 SSRs producing specific amplicons were ePCR-confirmed on multiple genomes i.e. Dabenzi, Taishanhong, AG2017 and Tunisia, resulting in identification of 63 polymorphic SSR markers (PIC ≥ 0.5). A subset of miRNA-SSRs (32) when assayed on six pomegranate genotypes, revealed their ability to detect higher polymorphism (89.29%). Furthermore, target prediction and network analysis suggested a possible association of miRNA-SSRs i.e. miRNA_SH69, miRNA_SH36, miRNA_SH103, miRNA_SH35 and miRNA_SH53 with seed hardness trait. These miRNA-SSRs would serve as important genomic resource for rapid and targeted improvement of seed hardness trait of pomegranate.